2013
DOI: 10.1155/2013/707438
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Thrombocytosis Associated with Acute Myocardial Infarction following STEMI with Percutaneous Coronary Intervention

Abstract: The etiology of thrombocytosis can be classified into reactive and essential forms. The rate of thromboembolic events is higher in essential thrombocytosis, and these events include strokes, transient ischemic attacks, retinal artery or retinal vein occlusions, digital ischemia, and acute coronary syndrome. In a study of 732 medical and surgical patients with thrombocytosis, 88% had reactive thrombocytosis. Patients with reactive thrombocytosis do not require cytoreductive medications or antiplatelet treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…32 Another mechanism involves the effect of hyperglycemia on platelets; this phenomenon was reported for diabetes patients with acute myocardial infarction by Oswald et al 32 Acute myocardial ischemia itself can cause reactive thrombocytosis; this phenomenon has been cited in 2 case reports in the literature. 33 Our study had limitations similar to those of other retrospective studies. Also, we were unable to discover the scorpion species, and information was missing from the medical records.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…32 Another mechanism involves the effect of hyperglycemia on platelets; this phenomenon was reported for diabetes patients with acute myocardial infarction by Oswald et al 32 Acute myocardial ischemia itself can cause reactive thrombocytosis; this phenomenon has been cited in 2 case reports in the literature. 33 Our study had limitations similar to those of other retrospective studies. Also, we were unable to discover the scorpion species, and information was missing from the medical records.…”
Section: Discussionmentioning
confidence: 69%
“…32 Another mechanism involves the effect of hyperglycemia on platelets; this phenomenon was reported for diabetes patients with acute myocardial infarction by Oswald et al 32 Acute myocardial ischemia itself can cause reactive thrombocytosis; this phenomenon has been cited in 2 case reports in the literature. 33…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al in 2019 and Geo et al in 2015 published two separate cases of patients with essential thrombocytosis of platelet level 1095×10 3 /μL and 600×10 3 /μL, respectively, causing hyperviscosity syndrome leading to a thrombus formation resulting in MI 7 8. Meanwhile, Dumrongmongcolgul et al published a case of a patient who developed a MI due to reactive thrombocytosis of platelet count of 966×10 3 /μL 9…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in another retrospective study comprising 129 patients with the platelet count over 1 mln/uL, Buss et al [12] showed a constant frequency of incidents of thrombosis among patients with myeloproliferative conditions and patients with RT. [1,[13][14][15][16][17]. The phenomenon of reactive thrombocytosis after splenectomy is the one best known so far.…”
Section: Discussionmentioning
confidence: 99%